Biosynthesis of surface-active compounds by Pseudomonas representatives - Кузьменко, А. В. (Problems of Environmental Biotechnology, 2013)
Biosurfactants are surface active biomolecules obtained by microorganisms and have a wide-range of applications. In this article the production and characterization of rhamnolipid biosurfactants produced by Pseudomonas representatives are described. Applications of rhamnolipid in the chemical industry, agriculture and bioremediation are evaluated. This review emphasizes the effect of nutritional and environmental factors on the biosurfactants synthesis. Also the use of cheaper raw materials for commercial production of rhamnolipid by Pseudomonas species are introduced.